PENGARUH GAYA HIDUP DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN INVESTASI (Studi Empiris pada Fakultas Ekonomi dan Bisnis Universitas Nusa Nipa) - Aemelia Antonetha Bira; Andreas Rengga; Yoseph Darius Purnama Rangga (Jurnal Projemen UNIPA, 2025)
This study aimed to examine and analyze the influence of lifestyle on investment decisions, the influence of risk perception on investment decisions, as well as the influence of lifestyle and risk perception simultaneously on investment decisions among lecturers of the Faculty of Economics and Business, Nusa Nipa University. The research method employed was quantitative associative with a survey approach. Data were collected through questionnaires distributed to 55 lecturers as respondents. The independent variables in this study were lifestyle (X1) and risk perception (X), while the dependent variable was investment decision (Y). Data analysis used multiple lincar regression with the assistance of SPSS version 23. The results showed that: (1) Lifestyle had a positive and significant effect on investment decisions with a regression coefficient of 1.428 and a significance value of 0.000; (2) Risk perception also had a positive and significant effect on investment decisions with a regression coefficient of 0.199 and a significance value of 0.000; (3) Simultaneously, lifestyle and risk perception had a significant effect on investment decisions with an F-count value of 177.338 and a significance value of 0.000. The coefficient of determination (R) of 0.872 indicated that 87.2% of the variation in investment decisions could be explained by lifestyle and risk perception, while the remaining 12.8% was influenced by other factors beyond this study